2018
DOI: 10.1071/rd17271
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin counteracts the effects of heat shock on the maturation of bovine oocytes

Abstract: The cellular mechanisms induced by elevated temperature on oocytes are not fully understood. However, there is evidence that some of the deleterious effects of heat shock are mediated by a heat-induced increase in reactive oxygen species (ROS). In this context, carotenoid antioxidants might have a thermoprotective effect. Therefore, the objective of this study was to determine the role of astaxanthin (AST) on oocyte ROS production and on the redox profile and developmental competency of cumulus-oocyte complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 75 publications
2
17
0
2
Order By: Relevance
“…It has been repeatedly demonstrated, both in the present experiments and by others, that heat shock increases ROS production by the bovine oocyte (Nabenishi et al, 2012;Ispada et al, 2018) and reduces the percentage of oocytes that cleave after coincubation with spermatozoa (Roth & Hansen, 2004a;de Castro e Paula & Hansen, 2007). In some cases, the deleterious actions of heat shock on the oocyte also compromise the ability of the subsequent embryo to develop to the blastocyst stage (Roth et al, 2004a,b;Nabenishi et al, 2012;Rodriques et al, 2016) although this consequence of heat shock has not always observed (de Castro e Paula & Hansen, 2007;Cebrian-Serrano et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been repeatedly demonstrated, both in the present experiments and by others, that heat shock increases ROS production by the bovine oocyte (Nabenishi et al, 2012;Ispada et al, 2018) and reduces the percentage of oocytes that cleave after coincubation with spermatozoa (Roth & Hansen, 2004a;de Castro e Paula & Hansen, 2007). In some cases, the deleterious actions of heat shock on the oocyte also compromise the ability of the subsequent embryo to develop to the blastocyst stage (Roth et al, 2004a,b;Nabenishi et al, 2012;Rodriques et al, 2016) although this consequence of heat shock has not always observed (de Castro e Paula & Hansen, 2007;Cebrian-Serrano et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
“…Heat shock may disrupt oocyte function, at least in part, by increasing the generation of reactive oxygen species (ROS). Production of ROS is increased by heat shock (Nabenishi et al , 2012; Ispada et al , 2018) and antioxidants such as retinol (Lawrence et al , 2004), cysteine (Nabenishi et al , 2012) and astaxanthin (Ispada et al , 2018) can reduce the negative consequences of heat shock on the oocyte. Moreover, the function of the maturing oocyte can be disrupted by other oxidative stresses, as shown for the nitric oxide donor sodium nitroprusside in the bovine (Soto et al , 2003; Cheuquemán et al , 2015) and hydrogen peroxide in the mouse (Tamura et al , 2008) and pig (Yazaki et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the basic factors is essential culture conditions of the oocyte during in vitro maturation (IVM) for normal maturation (Cetica et al, 2001). Maturating oocytes (Roth and Hansen 2004;Sen, 2014) in in vitro at high temperature (Lánská et al, 2006) (41 °C) were initiated cellular and molecular changes in the oocyte that causing to the decreased potential of development (Ispada et al, 2018). During maturation 12-14 h heat shock interrupted oocyte microtubule and microfilament texture (Roth and Hansen 2005) and spindle positioning (Ju et al 2005), diminished nuclear maturation (Roth and Hansen 2005;Rodrigues et al 2016), affection distribution of cortical granule (Maya-Soriano et al 2013) and reducing mitochondrial function in oocyte (Nabenishi et al 2012).…”
Section: Bspublishersmentioning
confidence: 99%
“…It has been studied for a long time to understand effect heat stress on mature and immature cattles oocytes and also it caused to infertility (Ispada et al, 2018). Cattle oocytes are susceptible to environmental condition factors such as heat stress, temperature and humidity…”
Section: Introductionmentioning
confidence: 99%
“…Бидний туршилтдаа ашигласан BO-IVM, BO-IVF, BO-IVC орчинд үр тогтооход үр тогтолтын хувь бусад орчноосоо харьцангуй өндөр байгаа нь цаашид энэхүү орчинг хэрэглэх нь илүү үр дүнтэй байх боломжтойг илэрхийлж байна. Өндгөн эсийг өсгөвөрлөх температур нь (41°C), астаксантинг 12.5 болон 25 nM хэмжээтэй уусмалд хийж өндгөн эсийг өсгөвөрлөхөд дулааны цочролоос үүсэх сөрөг нөлөө бага бластоцист шатанд хүрч сайн үр дүнтэй байсан бол 50nM астаксантин агуулсан үед эерэг нөлөө үзүүлдэггүй байна [15].…”
unclassified